Ionic Actuators as Manipulators for Microscopy - Must, Indrek; Rinne, Pille; Krull, Friedrich; Kaasik, Friedrich; Johanson, Urmas; Aabloo, Alvo (Frontiers in Robotics and AI, 2019)
Non-destructive handling of soft biological samples at the cellular level is becoming increasingly relevant in life sciences. In particular, spatially dense arrangements of soft manipulators with the capability of in situ monitoring via optical and electron microscopes, promises new and exciting experimental techniques. The currently available compliant manipulation technologies offer high positioning accuracy, yet these devices significantly grow in complexity in achieving this compliance and accuracy. We explore soft and compliant actuator material with a mechanical response similar to gel-like samples for perspective miniaturized manipulators. First, we demonstrate three techniques of rendering a bulk sheet-like electroactive material, the ionic and capacitive laminate (ICL), into a practical manipulator. We then show that these manipulators are also highly compatible with electron optics. Finally, we explore the performance of an ICL manipulator in handling a single large cell. Intrinsic compliance, miniature size, simple current-driven actuation, and negligible interference with the imaging technologies suggest a considerable perspective for the ICL in spatially dense arrays of compliant manipulators for microscopy.